Pengaruh Metode Estafet Writing Terhadap Kemampuan Menulis Cerita Pendek Pada Siswa Kelas IV Sekolah Dasar - Ningsih, Anggi Rahayu; Djunaidi; Eni Heldayani (Journal of Practice Learning and Educational Development, 2025)
Writing ability is one aspect of language skills that must be mastered by students, yet there are still several issues that make it difficult for students to write short stories, one of which is the limitation of the teaching methods used. The problem in this study is whether there is an influence of the Estafet Writing method on the writing ability of fourth-grade students at SD Negeri 78 Palembang for the academic year 2024/2025. The method used in this research is the experimental method. The sample of this study consists of 40 students (20 experimental class students and 20 control class students). Data collection techniques in this study include documentation and tests. The test results data were analyzed using prerequisite tests, followed by hypothesis testing using the t-test. Based on the learning outcome test, it is known that the average score of students in the experimental class is higher, namely 80.95 (good), compared to students in the control class, which is 70.05 (satisfactory), There is an influence of the Estafet Writing method on the short story writing skills of fourth-grade students at SD Negeri 78 Palembang. This is evident from the results of the hypothesis test using the t-test, where after analysis, it was obtained that (thitung) 4.309 > (table) 1.685, thus Ha is accepted and H0 is rejected. Therefore, there is an influence of the Estafet Writing method on the short story writing skills of fourth-grade students at SD Negeri 78 Palembang.